Study on Extension of Shelf Life Tomato using Controlled Atmosphere Storage - Davoodi, Mehdi Ghiafeh (Asian Journal of Biological and Life Sciences, 2017)
Investigations were carried out to study the effect of different gas compositions of Controlled Atmosphere (CA) on the shelf life and quality of tomato variety Red Cloud. Mature green tomatoes werehandpicked, sorted, washed, treated with permitted fungicide solution of known concentration and stored in CA conditions at 9+ 1°C, 90+ 5% RH using 5% O2, 1% CO2 and 5% O2, 2% CO2 with N2 as balance gas. Physicochemical and visual appearance of the tomatoes such as colour, texture, TSS, pH, acidity, sugars, pigments, ripening index and cumulative spoilage were periodically analysed. Results indicates that, tomato variety Red Cloud harvested at mature green stage could be stored in fresh and firm condition upto 8 weeks under CA conditions (5% O2 and 2% CO2 at 9+1C) as compared to 4 weeks in control in cold room at 9+1°C . Physiological loss in weight (PLW) as well as cumulative spoilage was reduced considerably in CA stored fruits. At the end of 8 weeks of storage under CA conditions, tomatoes could ripe normally and developed full red color in 5 days at room temperature. Physicochemical changes after ripening were also studied and organoleptic quality characteristics of ripe fruits after CA storage were found very good. The above method of CA storage can be used for export of tomato variety Red Cloud in CA conditions by ship to distant countries.
Keywords: Atmosphere; Controlled; Shelf life; Storage; Tomato